1983
DOI: 10.1093/ajcp/80.4.511
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Familial Mediterranean Fever with Cutaneous Vasculitis and Immune Complex Nephritis: Light, Electron, and Immunofluorescent Study of Renal Biopsy

Abstract: A 29-year-old patient suffering from familial Mediterranean fever developed severe myalgia and hematuria. Skin biopsy showed vasculitis. The kidney biopsy revealed diffuse proliferative and exudative glomerulonephritis. On immunofluorescent examination, IgM deposits accompanied by C3 were found in coarse granular peripheral distribution. Electron microscopy revealed glomerular subepithelial deposits. Familial Mediterranean fever with vasculitis and immune complex nephritis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 3 publications
0
19
0
2
Order By: Relevance
“…Given that, most of the FMF-associated vasculitis cases had MEFV gene mutations, contributing role of these mutations for vasculitis development may be considered in the pathogenesis. In line with this view, our literature search showed that most of the FMF patients reported in literature with coexistent HSV or PAN had [7,9,10,13,14,65,66] Medium vessel vasculitic diseases Polyarteritis nodosa [7, 8, 11-13, 15, 70, 71] Large vessel vasculitic diseases Unreported Unclassified vasculitic conditions Protracted febrile myalgia [16,60,[72][73][74] Behçet's disease [17,18,79] Cutaneous vasculitis [87,88] either homozygous or compound heterozygous M694V mutations. However, since many FMF patients carrying these mutations do not have associated vasculitis, we admit that this coexistence cannot solely be explained by the presence of MEFV gene mutations.…”
Section: Pioneering Reports About Fmf-vasculitis Associationmentioning
confidence: 66%
See 1 more Smart Citation
“…Given that, most of the FMF-associated vasculitis cases had MEFV gene mutations, contributing role of these mutations for vasculitis development may be considered in the pathogenesis. In line with this view, our literature search showed that most of the FMF patients reported in literature with coexistent HSV or PAN had [7,9,10,13,14,65,66] Medium vessel vasculitic diseases Polyarteritis nodosa [7, 8, 11-13, 15, 70, 71] Large vessel vasculitic diseases Unreported Unclassified vasculitic conditions Protracted febrile myalgia [16,60,[72][73][74] Behçet's disease [17,18,79] Cutaneous vasculitis [87,88] either homozygous or compound heterozygous M694V mutations. However, since many FMF patients carrying these mutations do not have associated vasculitis, we admit that this coexistence cannot solely be explained by the presence of MEFV gene mutations.…”
Section: Pioneering Reports About Fmf-vasculitis Associationmentioning
confidence: 66%
“…Various types of skin rashes including palpable purpura have also been reported in patients with FMF [87]. Among these skin rashes, only erysipelas-like erythema is pathognomonic for FMF.…”
Section: Cutaneous Vasculitismentioning
confidence: 99%
“…The occurrence of circulating immune complexes in 50% of FMF patients, complement consumption, defective inhibition of complement activation (C5a), and uncontrolled release of tumor necrosis factor (TNF) support the view that an immune-related mechanism plays a role [64,65,66]. The presence of immunoglobulins, C3, and fibrinogen in skin and kidney biopsies of some patients are interesting features.…”
Section: Fmf-associated Vasculitidesmentioning
confidence: 92%
“…In 10 to 70% of cases, dermatological abnormalities are present; these consist most commonly of erysipelas-like lesions [6,12,46,47] which involve the legs, ankles, and dorsum of the feet. Other manifestations are nodular rashes, Schonlein-Henoch purpura [5,46,47], urticaria [6,47], bullous lesions [48], and a vasculitis which is usually associated with an immune-complex nephropathy [49]. In addition, splenomegaly is present in about 30% of cases overall [11][12][13] and, like the arthropathy and dermatological lesions, is less frequent in Arab patients [18].…”
Section: Clinical Aspectsmentioning
confidence: 99%